1999
DOI: 10.1021/cm981141r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Magnetism of La15.9(2)Cr5.4(2)S32:  A Cr(III) Sulfide Containing d3-d3Cr2S912-Bioctahedra with Large Antiferromagnetic Coupling

Abstract: The ternary Cr(III) sulfide La15.9(2)Cr5.4(2)S32 contains d3-d3 face-shared bioctahedral Cr2S9 12- dimers (d Cr - Cr = 3.014(5) Å) alternately linked by two types of edge-bridged octahedral cluster units (La6S13 and La3.9Cr1.4S13) to form chains running parallel to the c-axis. Its oxidation state, structure, composition, and magnetism are discussed in terms of previous literature reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…9 For the early lanthanides (Ln = La-Gd), an orthorhombic phase was identified, while rare-earth ions drawn from later in the series (Tb-Tm) generally favour adoption of a Y 2 MnS 4 -type structure and a spineltype structure is also observed for Yb-containing phases. However, recent singlecrystal X-ray diffraction studies indicate greater complexity and reveal that the phases of nominal stoichiometry "La 2 CrS 4 " and "La 2 FeS 4 " are rhombohedral and better formulated La 15.9 Cr 5.4 S 32 10 and La 52 Fe 12 In this work we have sought to carry out a systematic study of the structural and magnetic properties of ternary erbium-chromium sulphides. The presence, or otherwise, of long-range magnetic order at low temperatures is correlated with the detailed structures determined by single-crystal X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…9 For the early lanthanides (Ln = La-Gd), an orthorhombic phase was identified, while rare-earth ions drawn from later in the series (Tb-Tm) generally favour adoption of a Y 2 MnS 4 -type structure and a spineltype structure is also observed for Yb-containing phases. However, recent singlecrystal X-ray diffraction studies indicate greater complexity and reveal that the phases of nominal stoichiometry "La 2 CrS 4 " and "La 2 FeS 4 " are rhombohedral and better formulated La 15.9 Cr 5.4 S 32 10 and La 52 Fe 12 In this work we have sought to carry out a systematic study of the structural and magnetic properties of ternary erbium-chromium sulphides. The presence, or otherwise, of long-range magnetic order at low temperatures is correlated with the detailed structures determined by single-crystal X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of La 32.66 T 11 S 60 (T = Mn and Fe) were subsequently determined in the non-standard monoclinic space group Bm (Collin & Laruelle, 1974), but it was later suggested that the symmetry of the structures is actually trigonal (Cenzual et al, 1990). More recently, an X-ray diffraction investigation of La 15.9 Cr 5.4 S 32 established that the correct space group for the structure type is R3m (Litteer et al, 1999). We report here the redetermination of`La 32.…”
Section: Commentmentioning
confidence: 66%
“…In the ®rst structures of this type to be determined, La 32.66 T 11 S 60 (T = Mn and Fe), the smaller cavity contains an implausible T 2 dumb-bell, and the sites at the edge of the cavity, equivalent to La1b in our structure, are 60±80% occupied (Collin & Laruelle, 1974). In the more recently published structure of La 15.9 Cr 5.4 S 32 , three sites just outside the smaller cavity are partially ®lled by La or Cr, with a total occupancy of approximately 90%, and one site inside the cavity is occupied by an S atom with a non-positive de®nite displacement ellipsoid (Litteer et al, 1999). An additional S atom is located inside the larger cavity, which remains empty in the other structures.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The new structure 132 of K 2 TeS 3 contains isolated [TeS 3 ] 2À anions (or grossly distorted TeS 6 ``octahedra'') and K cations in distorted octahedral coordination to S atoms. La 15.9(2) Cr 5.4(4) S 32 is a new chromium(III) sul¢de 133 and probably represents the phase previously described as La 2 CrS 4 . It contains [CrS 9 ] 12À bi-octahedra with very strong d 3 ^d3 antiferromagnetic coupling between the Cr 3 species.…”
Section: Sul¢des and Selenidesmentioning
confidence: 81%